Recognizing the Bias : Financial Cycles and Fiscal Policy - Budina, Nina (IMF Working Papers; Working Paper, 2015)
This paper argues that asset price cycles have significant effects on fiscal outcomes. In particular, there is evidence of debt bias-the tendency of debt to increase over the cycle- that is significantly larger for house price cycles than stand-alone business cycles. Automatic stabilizers and discretionary fiscal policy generally respond to output fluctuations, whereas revenue increases due to house price booms are largely treated as permanent. Thus, neglecting the direct and indirect impact of asset prices on fiscal accounts encourages procyclical fiscal policies.